Introduction to the Special Issue: Communication Intervention for Individuals with Complex Communication Needs. Issue 6 (November 2019) - Sigafoos, Jeff; Gevarter, Cindy
Individuals with complex communication needs are likely to experience considerable difficulties and challenges with everyday communication interactions due to limited use and understanding of natural speech. In this editorial, we review the nature of complex communication needs, describe the wide range of individuals who may experience such needs, and provide a brief history of behavioral approaches to addressing these needs. We also highlight the six papers in this special issue that contribute to the further understanding of the use of behavioral intervention approaches for addressing complex communication needs. These papers include one conceptual overview of aided augmentative and alternative communication (AAC) interventions for individuals with complex communication needs, four intervention studies addressing a range of communicative topographies (i.e., vocal speech, AAC, and a social messaging app), and one systematic review examining interventions that promote communicative response variability. These six papers highlight the diversity of complex communication needs and emphasize the importance of examining the efficacy of a wide range of individualized behavioral approaches that are matched to specific needs and goals.